2013
DOI: 10.1097/dad.0b013e31825f7efe
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Protein Deficiency is Common in Sebaceous Neoplasms and Suggests the Importance of Screening for Lynch Syndrome

Abstract: The association between Lynch syndrome and sebaceous neoplasms is well characterized. The absence of expression of mismatch repair proteins (MMRPs) by immunohistochemistry (IHC) is often used in other Lynch-associated tumors to guide testing. IHC for MLH1, PMS2, MSH2, and MSH6 was performed on 36 benign and malignant sebaceous neoplasms with the absence of one or more MMRP in 38.9% of cases. Among lesions with abnormal IHC, 71.4% were missing both MSH2 and MSH6, 21.4% lacked MLH1 and PMS2, and 7.1% lacked only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…In our SA cohort, MSH6 deficiency was the most prevalent aberration, occurring in combination with MSH2 deficiency in the vast majority of cases. This was also the observation in prior reports that include MSH6 examination [7][8][9][10]. Notably, in two of our 17 MMR-protein deficient SAs, loss of expression was confined to the MSH6, probably indicating MSH6 mutation, as was the case in three of the specimens (sebaceous adenomas and epitheliomas) in Chhibbar's series [7], as well as in 2 of 25 deficient sebaceous neoplasms of Cornejo et al [17], and in one of 26 SAs reported by Mojtahed et al [8].…”
Section: Msh6 Deficiencysupporting
confidence: 67%
See 4 more Smart Citations
“…In our SA cohort, MSH6 deficiency was the most prevalent aberration, occurring in combination with MSH2 deficiency in the vast majority of cases. This was also the observation in prior reports that include MSH6 examination [7][8][9][10]. Notably, in two of our 17 MMR-protein deficient SAs, loss of expression was confined to the MSH6, probably indicating MSH6 mutation, as was the case in three of the specimens (sebaceous adenomas and epitheliomas) in Chhibbar's series [7], as well as in 2 of 25 deficient sebaceous neoplasms of Cornejo et al [17], and in one of 26 SAs reported by Mojtahed et al [8].…”
Section: Msh6 Deficiencysupporting
confidence: 67%
“…We found, as have others [6][7][8][9][10]13,14,17,26] that MSH2/MSH6 deficiency, suggestive of MSH2 germline mutation, overrides other constellations. However, in the study by Entius et al [12], based on eight MMR-protein deficient SCs, the proportion of cases with loss of MSH2 and MLH1 was similar, which, as the authors acknowledged, might reflect bias by familiar clustering.…”
Section: Distribution Pattern Of Mmr-protein Deficienciessupporting
confidence: 52%
See 3 more Smart Citations